2012
DOI: 10.1080/10934529.2012.672074
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long-term cadmium exposure in turkeys: Accumulation and zinc prevention

Abstract: Experiments with turkeys were conducted to determine the effects of long-term ingestion of Cd (2.0 mg Cd/day/turkey) on its accumulation in the tissues and organs. The cadmium was found especially in the muscles, livers and kidneys. The highest average content of cadmium was found in the kidneys (1.09 mg/kg). The contents of Cd in the kidneys and livers were 19 times and 14 times (respectively) higher compared to the muscles. The administration of Zn (72 mg / day / turkey) along with high doses of Cd, signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…SeMet can be available for selenoprotein synthesis, be released from tissues, and be efficient in maintaining the GPX level ( 53 , 54 ). Newairy et al ( 58 ) also pointed out that the protective potential of Se may be associated with the recovery of GPX and SOD activities. We also found that Se improved SOD activity in the serum, GPX activity in the liver and GPX activity, and GSH concentration in the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…SeMet can be available for selenoprotein synthesis, be released from tissues, and be efficient in maintaining the GPX level ( 53 , 54 ). Newairy et al ( 58 ) also pointed out that the protective potential of Se may be associated with the recovery of GPX and SOD activities. We also found that Se improved SOD activity in the serum, GPX activity in the liver and GPX activity, and GSH concentration in the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…This theory was supported by Teshfam et al (2006), who indicated that administrations might affect the absorption of Cd into the body. Nad et al (2012) reported high Cd absorption affinity by somatic cells of kidney and liver of turkeys, while Li et al (2018) obtained low Cd absorption affinity of the laying hen ovary.…”
Section: Toxic Levels Of Cadmiummentioning
confidence: 99%
“…The selenium function to protect the renal and hepatic tissues against the toxicity of Cd is a result of lipid peroxidation reduction and increases the activities of antioxidant enzymes in these tissues (Newairy et al 2007). Selenium supplementation increased the essential minerals (Cr, Mn, Zn, and Se) and decreased toxic mineral (Cd, Li, and Pb) contents in kidney tissues of chickens, which were induced by Cd, suggesting that Se may decrease the negative effects of Cd and improve the trace mineral homeostasis in tissues of chickens (Zhang et al 2017a;Bao et al 2018).…”
Section: Reviewmentioning
confidence: 99%
“…In addition, Cd uptake toxicity can vary according to cell type in the kidneys and liver (Li et al, 2018;Olgun et al, 2020). Nad et al (2012) evaluated Cd absorption in turkeys and observed an intense accumulation of Cd in bones, muscles, liver, and kidneys. Similar results have been reported by other studies (Ali et al, 2016;Jin et al, 2018;Kar et al, 2018;Vasiljeva et al, 2018), suggesting that liver and kidneys are more sensitive to Cd accumulation.…”
Section: Introductionmentioning
confidence: 99%